Viral and cellular requirements for the budding of Feline Endogenous Retrovirus RD-114 - Fukuma, Aiko (BioMed Central, 2011)
BACKGROUND: RD-114 virus is a feline endogenous retrovirus and produced as infectious viruses in some feline cell lines. Recently, we reported the contamination of an infectious RD-114 virus in a proportion of live attenuated vaccines for dogs and cats. It is very difficult to completely knock out the RD-114 proviruses from cells, as endogenous retroviruses are usually integrated multiply into the host genome. However, it may be possible to reduce the risk of contamination of RD-114 virus by regulating the viral release from cells. RESULTS: In this study, to understand the molecular mechanism of RD-114 virus budding, we attempted to identify the viral and cellular requirements for RD-114 virus budding. Analyses of RD-114 L-domain mutants showed that the PPPY sequence in the pp15 region of Gag plays a critical role in RD-114 virus release as viral L-domain. Furthermore, we investigated the cellular factors required for RD-114 virus budding. We demonstrated that RD-114 virus release was inhibited by overexpression of dominant negative mutants of Vps4A, Vps4B, and WWP2. CONCLUSIONS: These results strongly suggest that RD-114 budding utilizes the cellular multivesicular body sorting pathway similar to many other retroviruses.